Decentralized robust adaptive output‐feedback control for a class of large‐scale stochastic time‐delay nonlinear systems with dynamic interactions. Issue 3 (21st April 2020) - Wang, Qiangde; Wang, Qian; Wei, Chunling; Wang, Hui; Liu, Shaoning
Abstract: The paper solves the problem of decentralized robust adaptive output‐feedback control for a class of large‐scale stochastic time‐delay nonlinear systems. Under the assumptions that the inverse dynamics of the subsystems are stochastic input‐to‐state stable, an adaptive output‐feedback controller is constructively designed by the back‐stepping method. It is shown that under some milder conditions, the closed‐loop system is globally stable in probability and the outputs can be regulated to an arbitrarily small neighborhood of the origin in probability and other signals in the closed‐loop system are global bounded in probability by selecting the design parameters and appropriate Lyapunov function. A simulation example is presented to illustrate the effectiveness of the designed controller.